No evidence for altered plasma NGF and BDNF levels in fibromyalgia patients - Baumeister, David; Eich, Wolfgang; Saft, Silvia; Geisel, Olga; Hellweg, Rainer; Finn, Anja; Svensson, Camilla I.; Tesarz, Jonas (Scientific reports, 2019)
There has been a surging interest in the putative role of peripheral growth factors in the pathophysiology of fibromyalgia, specifically in the peripheral sensitization that occurs in chronic pain disorders. This cross-sectional study set out to assess and compare brain-derived neurotrophic factor (BDNF) and nerve growth factor (NGF) in plasma samples from fibromyalgia patients and healthy controls. Plasma BDNF and NGF were measured in 89 fibromyalgia patients and 36 pain-free controls, and compared using ANCOVA controlling for potential confounders, as well as Bayesian methods for parameter estimation and model evaluation. BDNF and NGF levels in fibromyalgia patients did not differ from those in pain-free controls. Statistical methods were consistent, with both frequentist and Bayesian approaches leading to the same conclusions. Our study fails to replicate the finding that peripheral BDNF is altered in fibromyalgia, and instead our findings suggest that plasma levels of growth factor appear normative in fibromyalgia.
Gesehen am 21.02.2020